3
$\begingroup$

(Problem 13 of Milnor's Topology from the differentiable viewpoint).

Let $M^n,N^m\subset \mathbb{R}^{m+n+1}$ be compact, oriented differential manifolds without boundary of dimension $n$ and $m$.

Consider

$\phi:M^n \times N^m\rightarrow S^{n+m}:(p,q)\mapsto \frac{q-p}{||q-p||}$

and define $l(M,N)=$deg$(\phi)$. I would like to prove $l(M,N)=(-1)^{(m+1)(n+1)}l(N,M)$.

So far I did the following. Define

$\phi_1:M^n \times N^m\rightarrow S^{n+m}:(p,q)\mapsto \frac{q-p}{||q-p||}$

and

$\phi_2:N^m \times M^n\rightarrow S^{n+m}:(q,p)\mapsto -\frac{q-p}{||q-p||}$.

We want deg$(\phi_1)=$deg$(\phi_2)$. Let $z$ be a regular value of $\phi_1$. If I am correct this means that $-z$ is a regular value of $\phi_2$. Moreover $\phi_1^{-1}(z)$ and $\phi_2^{-1}(-z)$ are in one to one correspondence via $(p,q)\mapsto (q,p)$. Therefore we are left to show for each such $(p,q)$:

sgn$(\phi_1,(p,q)) = (-1)^{(m+1)(n+1)}$sgn$(\phi_2,(q,p))$

where sgn$(\phi_1,(p,q))$ is +1 if the derivative map $(d{\phi_1})_{(p,q)}$ preserves orientation and -1 otherwise.

I am stuck proving this last equality. It looks like the antipodal map but theres is some change of coordinates going as well. I think I am messing up working with different orientations. Does anyone know how to proceed? Thank you for your help!

$\endgroup$
  • $\begingroup$ So $M$ and $N$ are submanifolds of $\Bbb R^{m+n+1}$? $\endgroup$ – Lord Shark the Unknown May 30 '17 at 17:44
  • $\begingroup$ Yes indeed! Sorry for the confusion, I'll edit my question. $\endgroup$ – PP123 May 30 '17 at 17:46
  • $\begingroup$ $\phi_2 = \phi_1 \circ c$ where $c : N \times M \to M \times N$ is the map which switches the factors. What is the degree of $c$? $\endgroup$ – Balarka Sen May 30 '17 at 18:03
  • $\begingroup$ The degree of c should be just sgn$(c,(q,p))$ for some $(q,p) \in N \times M$. Then for $(v_n,v_m)\in T_{(q,p)}(N \times M)= T_q M \times T_p N$ we get $dc_{(q,p)}(v_n,v_m)=(v_m,v_n)$. But then I get for (n_1,...,n_m) base of $T_qN$ and $(m_1,...,m_n)$ base of $T_pM$ and thus $\{(n_1,0),...,(0,m_n)\}$ as base for $T_{q,p}(N\times M): \frac{s(dc(n_1,0)),...,dc(0,m_n))}{s((n_1,0),...,(0,m_n))}=\frac{s((0,n_1),...,(m_n,0))}{(n_1,0),...,(0,m_n)}$. But how do I work this further out? $\endgroup$ – PP123 May 30 '17 at 18:22
4
$\begingroup$

As Milnor suggests, let the linking map be $$\lambda:M^m\times N^n\to S^k,$$ $$\lambda(p,q)=\dfrac{p-q}{||p-q||},$$ with $m+n=k$, where $M,N\subset\mathbb{R}^{k+1}$ are disjoints, oriented, boundaryless manifolds. Define $$\lambda':N^n\times M^m\to S^k,$$ $$\lambda'(q,p)=\dfrac{q-p}{||q-p||}=-\dfrac{p-q}{||p-q||}$$ the linking map of interest. Let $\phi:S^k\to S^k$ be the antipodal map. We see that we have $\lambda(p,q)=(\phi\circ\lambda')(q,p)$ for all $p\in M$ and $q\in N$. Taking into account the reversal map given by $$ \psi:M^m\times N^n\to N^n\times M^m$$ which maps $(p,q)$ to $(q,p)$ and has degree $(-1)^{mn}$, we can proceed. We have $\lambda=\phi\circ\lambda'\circ\psi$.

Thus, as problem 1 of Milnor suggests, $$\mathrm{deg}(\lambda)=\mathrm{deg}(\phi)\mathrm{deg}(\lambda')\mathrm{deg}(\psi).$$

Hopf theorem of section 7 and the end of section 5 of Milnor can help you now. We know that for $k$ odd, the antipodal map is homotopic to the identity but for $k$ even, it isn't. So, it is easily shown that $$\mathrm{deg}(\phi)=(-1)^{k+1}.$$ It then follows that $$\mathrm{deg}(\lambda)=(-1)^{n+m+1+mn}\mathrm{deg}(\lambda')=(-1)^{(m+1)(n+1)}\mathrm{deg}(\lambda')$$ which is what we wanted to show.


EDIT: I think I need to further explain what is up with this reversal map.

Problem 8 in milnor shows that for two smooth manifolds, we have $$T_{(x,y)}(M\times N)=T_x M\times T_y N.$$ With this in mind, the differential of the reversal map can be formulated as $$(v_1,\dots, v_m,w_1,\dots, w_n)\mapsto (w_1,\dots w_n,v_1,\dots, v_m).$$ You can show that the determinant of this linear application is $(-1)^{mn}$ by counting permutations. I hope this helps.

$\endgroup$
  • $\begingroup$ I don't see why $\lambda = \phi \circ \lambda$ '. $\lambda$ works on $M \times N$ and$ \phi \circ \lambda$ ' on $N \times M$... $\endgroup$ – PP123 May 30 '17 at 18:28
  • $\begingroup$ I see exactly you concern. I will edit my post. $\endgroup$ – Alexis Leroux-Lapierre May 30 '17 at 18:32
  • $\begingroup$ You also need to take into account the degree of the reversal map from $M\times N$ to $N\times M$ which is $(-1)^{mn}$. $\endgroup$ – Lord Shark the Unknown May 30 '17 at 18:33
  • $\begingroup$ Yes, I am seeing this right now. $\endgroup$ – Alexis Leroux-Lapierre May 30 '17 at 18:33
  • $\begingroup$ I corrected it, thank you @LordSharktheUnknown for the comment. $\endgroup$ – Alexis Leroux-Lapierre May 30 '17 at 18:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.